Comparative Study of Student Performances from Two Socioeconomic Backgrounds: Kwambai Primary School - Iroka, Jude; Akpienbi, Isaac Oritsejubemi (International Journal of Education, Management, and Technology, 2024)
Purpose of the project is to study the performances of students from two socio-economic backgrounds. The method used was t-test. The parameters of the t-test were estimated using R software. The results showed that there is no significant difference in the performances of students from these two socio-economic status. Performances are functions of personal motivation and resilience. Support systems and enabling environment also play crucial rules in academic achievement.